OPTIMALISASI KONSENTRASI PUPUK ORGANIK CAIR BIOGUSUAN TERHADAP RESPON PERTUMBUHAN VEGETATIF TANAMAN SAWI HIJAU (Brassica juncea L.) - Subrata, I Made; I Wayan Suanda; Venansia Nina; I Nengah Suka Widana (Emasains : Jurnal Edukasi Matematika dan Sains, 2024)
Liquid organic fertilizer is a complete fertilizer because it contains macro and micro elements. The purpose of this study was to determine whether there was an influence or concentration of Bio GuSuan liquid organic fertilizer on the vegetative growth response of mustard greens (Brassica juncea L.). This research is an experimental research. The independent variables is the concentration of liquid organic fertilizer, namely the concentration of 1%; 2%;3%;4%; 5%, and control (0%). Data analysis used statistical analysis with one way analysis of variance (ANOVA) test with a significance level of 5%. Based on the results of data analysis, it can be concluded: (1) There is an effect of Bio GuSuan liquid organic fertilizer on the vegetative growth of mustard greens (Brassica juncea L), (2) Bio GuSuan liquid organic fertilizer with a concentration of 5% in treatment (T5) is the most optimal concentration for the vegetative growth of mustard greens (Brassica juncea L). Leaf area is 5.2 and the number of leaves is 3,800. Based on the F table value with a significance level of 5%, (the sum of inter =3 and the sum of inner =20), the H0 rejection limit is 3.10.